Ecological zipper: the use of ecologies to produce an architectural response and its role in sustainable development - Whyte, Ross (My University, 2011)
The following thesis looks at the role of ecologies in architecture and its role in sustainable development. The purpose of the work is to create an architectural response which provides the urban and natural realm with a positive outcome where by users of the architecture experience a zipping together of the man made and the natural connecting them creating a unique threshold to gain a fuller understanding and appreciation of their surrounding natural environment. The work involved the study of ecosystems and their relation to sustainable development. What the research has led to is a further understanding of the degree in which buildings interact and allow the users to interact with nature. The resultant architectural solution drives the interaction a building traditionally has with its environment, from the establishment of a program through to detailing to promote sustainable development on a broad scale.